EKOWISATA BERBASIS KONSERVASI BEKANTAN - El Faruqy, Javied; Muchamad, Bani Noor (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
Proboscis monkey is mascot animal of South Borneo that is going through population decrease and considered as endangered animal. There is required effort with aim to preserving these animals. One of the conservation programs that can be implemented is nature based-tourism development with proboscis monkey as the object. In order to support this program, a proboscis monkey conservation based-ecotourism is designed with aim to educate about importance of proboscis monkey preservation. The designed object spread on two points, that is Muara Kanoco Village and Curiak Island that had been appointed by SBI as ecotourism area. This ecotourism emphasize on educative concept with human-nature symbiosis method. Educative concept is making the nature as learning space, while human-nature symbiosis is making human and nature have a good reciprocal relationship..